2007
DOI: 10.1063/1.2821754
|View full text |Cite
|
Sign up to set email alerts
|

Domain size effects in a uniaxial ferroelectric relaxor system: The case of SrxBa1−xNb2O6

Abstract: We present investigations of the domain dynamics and of the evolution of the critical exponent β in a ferroelectric relaxor system, exemplarily in the up-to-date controversial strontium barium niobate (SBN). k-space spectroscopy at the phase-transition and when applying an electric field reveals a size-dependent response of the domains. This is supported by pyroelectric measurements that show, by analysis in terms of criticality, the critical exponent β is not only dependent on the level of poling but also on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…4 literally, as relaxors are never formally in thermal equilibrium. 22,26,27 However, the FH data suggests the intriguing possibility of a large ⌬T =9 K at 25°C when E = 723 kV cm −1 is applied. This is an interesting outcome because no dielectric material has shown or been predicted to show such a large ECE at room temperature.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…4 literally, as relaxors are never formally in thermal equilibrium. 22,26,27 However, the FH data suggests the intriguing possibility of a large ⌬T =9 K at 25°C when E = 723 kV cm −1 is applied. This is an interesting outcome because no dielectric material has shown or been predicted to show such a large ECE at room temperature.…”
mentioning
confidence: 95%
“…1. Failure of the dielectric behavior above T m to collapse to a single frequency-independent curve could be simply due to sampling in a small temperature window, or due 21 to space charge associated with low crystallinity, or due [21][22][23] to inhomogeneity such that the transition is smeared out. The discrepancy in the absolute value of the calculated permittivity at 1 kHz ͑ϳ5%͒ ͑between Fig.…”
mentioning
confidence: 99%
“…In preparation, the crystal was first heated up above the Curie temperature T c ≈ 70-80°C and then cooled down without applying an electric field to produce an unpoled sample. In order to influence the domain size and form, the sample was subsequently poled and repoled stepwise at room temperature [12,16]. For this, an electric field was applied along the polar axis and increased in steps of 10 V=cm every 2 s until finally 7:5 kV=cm are reached.…”
mentioning
confidence: 99%
“…11 It has also been demonstrated that noncollinear second-harmonic generation in SBN can be used to characterize femtosecond laser pulses. [12][13][14] As the angular spectrum of planar SHG is directly related to the domain distribution this process can be used for k-spectroscopy 15,16 and to examine the switching behavior of ferroelectric domains. [17][18][19] Aside from noncollinear SHG the generation of the third harmonic via a cascaded χ (2) -process is also possible.…”
Section: Introductionmentioning
confidence: 99%